The American Psychiatric Association Publishing textbook of mood disorders - Nemeroff, Charles B.; Schatzberg, Alan F.; Rasgon, Natalie L.; Strakowski, Stephen M. (American Psychiatric Association Publishing, 2022)
"The second edition of The American Psychiatric Association Publishing Textbook of Mood Disorders is a book for a new generation of clinicians, trainees, and educators. Much has changed in the field of mood disorders in the 16 years since the first edition, and this new edition ably covers these changes, introducing new chapters on the epigenetics of mood disorders; the role of the immune system in these disorders; the contribution of childhood maltreatment to mood disorder risk, illness course, and treatment response; the management of treatment-resistant depression; and the emergence of promising investigational agents (most notably, ketamine and its relatives) with novel mechanisms of action in depression. Under new editorial direction and with a revised roster of expert contributors, The American Psychiatric Publishing Textbook of Mood Disorders, Second Edition, provides an authoritative, comprehensive, and evidence-based synthesis of current knowledge in the multifaceted field of mood disorders"--